Building Better Behaviour in the Early Years. - Smith, Maggie (Hands on Guides., 2009)
Every early years setting strives to create a calm and positive atmosphere, where children can thrive and develop as successful and confident learners. By asking you to reflect on how the ethos, practice and general approach in your setting impacts on the behaviour of both children and adults, this book suggest sensible ways to achieve an exciting and stimulating environment for all. From an award-winning author team, there is down-to-earth advice, a number of common-sense solutions and all the essential information you will need to develop the best sort of setting, where everyone supports one.